Electrical and magnetic properties of new compounds of the conductor anion [Ni(dmit)2]- and nitronyl nitroxide magnetic radicals - Dias,Mauro Cesar (2007)
Three compounds have been synthesized with formulae [3-MeRad][Ni(dmit)2] (1), [4-MeRad][Ni(dmit)2] (2) and [4-PrRad][Ni(dmit)2] (3) where [Ni(dmit)2]- is an anionic pi-radical (dmit = 1,3-dithiol-2-thione-4,5-dithiolate) and [3-MeRad]+ is 3-N-methylpyridinium alpha-nitronyl nitroxide, [4-MeRad]+ is 4-N-methylpyridinium alpha-nitronyl nitroxide and [4-PrRad]+ is 4-N-propylpyridinium alpha-nitronyl nitroxide. The temperature-dependent magnetic susceptibility of 1 revealed that an antiferromagnetic interaction operates between the 3-MeRad+ radical cations with exchange coupling constants of J1 = - 1.72 cm-1 and antiferromagnetism assigned to the spin ladder chains of the Ni(dmit)2 radical anions. Compound 1 exhibits semiconducting behavior and 3 presents capacitor behavior in the temperature range studied (4 - 300 K).